A repeated cross‐sectional study of the epidemiology of Campylobacter and antimicrobial resistant Enterobacteriaceae in free‐living Canada geese in Guelph, Ontario, Canada. (4th October 2018) - Vogt, Nadine A.; Pearl, David L.; Taboada, Eduardo N.; Reid‐Smith, Richard J.; Mulvey, Michael R.; Janecko, Nicol; Mutschall, Steven K.; Jardine, Claire M.
Abstract: From May through October 2016, we conducted a repeated cross‐sectional study examining the effects of temporal, spatial, flock and demographic factors (i.e. juvenile vs. adult) on the prevalence of Campylobacter and antimicrobial resistant Enterobacteriaceae among 344 fresh faecal samples collected from Canada geese ( Branta canadensis ) from four locations where birds nested in Guelph, Ontario, Canada. The overall prevalence of Campylobacter among all fresh faecal samples was 9.3% and was greatest in the fall when these birds became more mobile following the nesting season. Based on 40 gene comparative genomic fingerprinting (CGF40), the increase in prevalence noted in the fall was matched by an increase in the number of unique CGF40 subtypes identified. Resistance to colistin was detected most commonly, in 6% of Escherichia coli isolates, and was highest in the late summer months. All colistin‐resistant isolates were negative for the mcr‐1 to mcr‐5 genes; a chromosomal resistance mechanism (PmrB) was identified in all of these isolates. The prevalence of samples with E. coli exhibiting multi‐class resistance or extended spectrum beta‐lactamase was low (i.e. <2% of samples). The intra‐class correlation coefficients, estimated from the variance components of multilevel logistic regression models, indicated that the shedding of Campylobacter and antimicrobial resistant E. coli among geese within a flock (i.e. birds collected from the same site on the same day) was moderately correlated. Spatial, temporal, and spatiotemporal clusters identified using the spatial scan statistic, largely supported the findings from our multi‐level models. Salmonella was not isolated from any of the fresh faecal samples collected suggesting that its prevalence in this population of birds was very low.